Effects of genetic and environmental factors and gene-environment interaction on expression variations of genes related to stroke in rat brain - Tan, Yuan D.; Fornage, Myriam (Scientific Research Publishing, 2011)
To determine if genetic and environmental (dietary) factors and gene-environment interaction impact on the expression variation of genes related to stroke, we conducted microarray experiments using two homozygous rat strains SHRSR and SHRSP fed with high and low dietary salt levels. We obtained expression data of 8,779 genes and performed the ranking analysis of microarray data. The results show that the genetic difference for stroke in rat brain has a strong effect on expression variations of genes. At false discovery rate (FDR) ≤ 5%, 534 genes were found to be differentially expressed between the genotypes resistant and prone to stroke, among which 304 genes were up-regulated in the resistant genotype and down-regulated in the prone genotype and 230 were down-regulated in the former and up-regulated in the latter. In addition, 365 were functional genes for transcription and translation, receptors (in particular, neurotransmitter receptor), channels of ions, transportation, metabolism and enzymes, and functional and structural proteins. Some of these genes are pivotal genes that cause stroke. However, dietary salt levels and GE interaction do not strongly impact on the expression variations of these genes detected on arrays.
Keywords: Rat; Ischemia Stroke; Microarray; Differential Expression; Genotype; Environment Factor; GE- Interaction